Circulating growth differentiation factor‐15 as a novel biomarker in heart transplant - Nithi Tokavanich; Supanee Sinphurmsukskul; Narisorn Kongruttanachok; Kanokwan Thammanatsakul; Supaporn Sritangsirikul; Aekarach Ariyachaipanich; Pat Ongcharit; Sarawut Siwamogsatham; Smonporn Boonyaratavej; Sarinya Puwanant (ESC Heart Failure, 2021)
Abstract Aims This study aimed to examine (i) whether circulating growth differentiation factor‐15 (GDF‐15) is associated with acute cellular cardiac allograft rejection (ACR); (ii) a longitudinal trend of GDF‐15 after heart transplantation; and (iii) the prognostic value of GDF‐15 in predicting a composite outcome of severe primary graft dysfunction (PGD) and 30 day mortality post‐transplant. Methods and results Serum samples were collected before heart transplantation and at every endomyocardial biopsy (EMB) post‐heart transplantation in de novo transplant patients. A total of 60 post‐transplant serum samples were matched to the corresponding EMBs. Seven (12%) were considered International Society for Heart Lung Transplantation Grade 1R ACR, and one (2%) was identified as Grade 2R ACR. GDF‐15 levels in patients with ACR were not different from those in the non‐rejection group (6230 vs. 6125 pg/mL, P = 0.27). GDF‐15 concentration gradually decreased from 8757 pg/mL pre‐transplant to 5203 pg/mL at 4 weeks post‐transplant. The composite adverse outcome of PGD and 30 day mortality was significantly associated with increased post‐operative GDF‐15 (odds ratio: 40; 95% confidence interval: 2.01–794.27; P = 0.005) and high inotrope score post‐transplant (odds ratio: 18; 95% confidence interval: 1.22–250.35; P = 0.01). Conclusions Circulating GDF‐15 concentration was markedly elevated in patients with end‐stage heart failure and decreased after heart transplantation. GDF‐15 was significantly associated with post‐transplant PGD and mortality. A lack of association between ACR and GDF‐15 did not support routine use of GDF‐15 as a biomarker to detect ACR. However, GDF‐15 may be potentially useful to determine heart transplant recipients at high risk for adverse post‐transplant outcomes. We suggest that GDF‐15 levels in recipient serum can provide risk stratification for severe PGD including death during post‐operative period. This novel biomarker may serve to inform and guide timely interventions against severe PGD and adverse outcomes during the first 4 weeks after transplantation. Further studies to support the utility of GDF‐15 in heart transplantation are required.